Linked USDL Extension for Describing Business Services and Users' Requirements in a Cloud Context - Benfenatki, Hind; Ferreira da Silva, C.; Benharkat, Aïcha-Nabila; Ghodous, P.; Maamar, Zakaria (International Journal of Systems and Service-Oriented Engineering, 2017)
Linked Unified Service Description Language (Linked USDL) provides a comprehensive way for describing services from operational, technical, and business perspectives. However, this description treats services as isolated components that offer functionalities only without emphasis on how they are used. This paper discusses how to extend Linked USDL in a way that permits to describe the services of a marketplace in support of automating the provisioning of service-oriented cloud-based business applications along with satisfying users' requirements. The marketplace consists of business services that can be composed and specialized services that act on behalf of the infrastructure upon which these applications are deployed. A set of experiments demonstrating the use of the extended Linked USDL are also presented in the paper.